Lessons from forestry decentralisation - Larson, A.M.; Ribot, J.C. (Center for International Forestry Research, 2009)
REDD+ is more likely to be just and locally legitimate if the design, implementation and allocation of benefits represent local needs and aspirations. Decentralisation of meaningful decisions to locally accountable and responsive (e.g., representative) local authorities would promote local engagement in REDD+ decision making. The level at which rules are made and benefits distributed will be a key issue in the legitimacy, effectiveness, efficiency and equity of REDD+.